Implementation of the internal auditor policy of the North Sulawesi Regional Police in the South Minahasa Resort Police - Liwutang, Verry A.; Kairupan, Sisca Beatrix; Mokat, Jetty E. H. (Technium Social Sciences Journal, 2024)
This study aims to analyze and evaluate the implementation of internal auditor policies carried out by the Regional Supervisory Inspectorate (Itwasda) of the North Sulawesi Regional Police in the South Minahasa Resort Police. Internal auditors have an important role in ensuring accountability, transparency, and operational effectiveness in the police environment, especially related to budget management, compliance with procedures, and implementation of tasks according to applicable operational standards. This research uses a qualitative approach with descriptive method, which involves data collection through in-depth interviews, observation, and document analysis. The research findings show that the process of implementing the internal auditor policy at South Minahasa Police Station has been running, but there are still some obstacles such as the lack of human resources trained in auditing, less than optimal communication between auditors and audited parties, and limited technology used in conducting audits. Nevertheless, the support from the leadership of the Resort Police and Itwasda North Sulawesi is a significant supporting factor in ensuring that audit recommendations can be implemented. The conclusion of this study emphasizes the need to increase the capacity of internal auditors through continuous training, improvement of supporting technology, and optimization of communication and collaboration between auditors and audited parties. With these corrective measures, it is expected that the effectiveness and efficiency of internal audits within the South Minahasa Police can be further improved, thus helping to achieve better governance in the police institution.